Association Between Positive Childhood Experiences and Caregiver-Reported ADHD Diagnosis and Severity - Crouch, Elizabeth; Radcliff, Elizabeth; Boswell, Emma; Brown, Monique J; Hung, Peiyin (Journal of developmental and behavioral pediatrics, 2024)
Little is known about the prevalence of positive childhood experiences (PCEs), a counter to adverse childhood experiences, in children with an attention-deficit hyperactivity disorder (ADHD) diagnosis. The purpose of this study was to examine the relationship between PCEs and ADHD diagnosis and severity, adjusting for child, family, and household characteristics, using a nationally representative data set. Using the 2020 to 2021 National Survey of Children's Health, our sample included children 6 years of age or older, as this is the age at which PCE questions are asked (n = 56,224). Multivariable logistic regression was used to examine the association between PCE type and ADHD diagnosis and severity, controlling for child and household characteristics. In multivariable regression analyses, children who had volunteered in their community had lower odds of a reported ADHD diagnosis than children who had not volunteered in their community (adjusted odds ratio [aOR] 0.83; 95% confidence interval [CI], 0.73-0.95). Children with a connected caregiver had a lower likelihood of ADHD diagnosis than children without a connected caregiver (aOR 0.66; 95% CI, 0.58-0.74). Children reporting moderate to severe ADHD were less likely to report exposure to any of the 7 PCEs examined, when compared with children reporting mild ADHD. The findings from this study can be important for clinicians and families to mitigate the negative social and academic outcomes that children with ADHD may face.